Differences In Interleukin-6 and Liver Enzyme Level Based On Clinical Severity of COVID-19 Patients at Dr. M. Djamil General Hospital, Padang - Elsesmita, Elsesmita; Medison, Irvan; Herman, Deddy (Respiratory Science, 2025)
Background: COVID-19 pathogenesis involves the release of proinflammatory cytokines and chemokines, known as a "cytokine storm." Interleukin-6 (IL-6) plays a key role in initiating cytokine storms. Cytokine storm causes multiple organ complications. Liver injury affects 14% to 53% of COVID-19 patients and is manifested by increased liver enzymes. This study evaluated differences in IL-6 and liver enzyme levels based on clinical severity in COVID-19 patients. Method: A retrospective cross-sectional study was conducted. COVID-19 patients treated at Dr. M. Djamil General Hospital, Padang, from January 1, 2021, to December 31, 2021, and who met the inclusion and exclusion criteria, were the research subjects. The Kruskal-Wallis test was performed to analyze differences in IL-6, SGOT, and SGPT levels based on clinical severity. Results: Most participants (42.06%) were under 50 years old, half were female (56.15%), obesity was the most common comorbidity (41.39%), and moderate severity was most common (42.06%). The majority of the subjects, 87.47%, had elevated IL-6 levels (≥7 pg/mL). SGOT levels of ≥32 IU/L (46.76%) and SGPT levels of ≥31 IU/L (41.39%) were found in less than half of the subjectsClinical severity was significantly associated with IL-6 levels, resulting in a significant difference in IL-6 levels (P<0.05). The clinical severity of COVID-19 patients at Dr. M. Djamil General Hospital, Padang, resulted in a significant difference in SGOT and SGPT levels (P<0.05). Conclusion: IL-6 levels differed based on clinical severity in COVID-19 patients. SGOT and SGPT levels also differed by clinical severity.